Simulation Of A Two-Stroke Spark Ignition Free Piston Linear Engine Motion - Mohamed, N. A. N.; Ariffin, A. K.; Fonna, S. (Penerbit UTM Press, 2006)

(untitled)
Two-Stroke Spark Ignition Free Piston Linear Engine Concept Is Analyzed In This Paper. The Main Components Of The Engine Are Combustion Chamber, Scavenging Chamber, Kickback Chamber And Slider-Piston. Dynamic And Thermodynamic Models Of The Slider-Piston Motion Are Presented. Also, The Effect Of Various Heat Additions And Compression Ratio On The Slider-Piston Velocity, Time Taken For One Stroke, And Stroke Length Are Explored. By Using Selected Engine Variables, The Motion Of The Two-Stroke Free Piston Linear Engine Is Successfully Simulated. The Results Show That The Velocity Profile Of Slider-Piston Motion Is Non-Sinusoidal. By Varying The Amount Of Heat Addition, The Velocity And Stroke Length Of Slider-Piston Will Increase Accordingly. However, By Increasing Compression Ratio, The Velocity Of Slider Piston Is Noted To Increase But The Stroke Length Of Slider-Piston Remains Constant.